Efficacy of Mindfulness Yoga on Mood and Self-compassion of Person with Mental Illness Living in a Community as a Pilot Study (Asian Journal of Social Science Studies, 2023)
Persons with mental illness feel symptoms like depression, anxiety, or fatigue. It is important for them to decrease symptoms and increase well-being. The present study investigated efficacy of mindfulness yoga on mood and self-compassion of persons with mental illness. Participants were persons with mental illness who lived in a community. Thirteen participants received once mindfulness yoga practice for 60 hours in a welfare facility. They completed POMS 2 (Profile of Mood Scale) and Self-Compassion Scale. Anger-Hostility, Confusion-Bewilderment, Fatigue-Lethargy, Tension-Anxiety significantly decreased. Self-kindness of Self-Compassion Scale significantly increased. Impression for participating for this program were “Refreshed both mentally and physically” or “Relaxed” and so on. These results suggest that the Mindfulness Yoga may be useful to maintain mood comfortable and increase self-compassion partially of persons with mental illness living in community.